Pengaruh Perceived of Technology dan Self-Efficacy terhadap Kemampuan Adopsi Teknologi dan Digitalisasi dalam Proses Pembelajaran : The Influence of Perceived Technology and Self-Efficacy on the Ability to Adopt Technology and Digitalization in the Learning Process - Novika Nala Ngoma; Filemon Zendrato; Beriman Nahampun; Nurmayuci Siregar; Zakarias Holo Kadja; Diana Manudjawa (ITScience (Information Technology and Science), 2024)
Digital technology has revolutionized many aspects of life in recent decades, including education. Conventional teaching methods are increasingly being replaced by more participatory, interactive, and technology-based approaches. The digitalization of education involves using new devices and demands a change in perspective, increased competence, and flexibility in facing evolving trends. In this context, this study aims to explore how teachers' perceptions of technology and their level of self-efficacy affect their ability to integrate technology into classroom teaching. One of the key factors in creating effective education in the digital era is the readiness and willingness of educators to adopt technology. This study used a quantitative survey method involving 150 teachers as respondents. Data were collected through a questionnaire that measured perceptions of technology, levels of self-efficacy, and the extent to which technology has been adopted in the learning process. The results showed that positive perceptions of technology and confidence in using it were the main factors in the success of technology integration in the classroom. The findings also revealed that teachers need intensive training to effectively understand and feel more comfortable using technology. Thus, this research is expected to be the basis for developing more structured policies and training programs to improve technology integration in education and support more innovative and practical learning in the future.